GeoGebra, Classroom y evaluaciones auto-corregibles en la enseñanza superior - Renjifo Salazar, Alex Xavier (2021)
This workshop was developed virtually, making use of personal computers, since it is intended that participants make constructions using GeoGebra software, with the possibility of making immediate changes that allow identifying the invariant properties of mathematical objects. The session emphasizes practical emphasis and includes individual or cooperative activities, in order to promote discussion and exchange of solution strategies for the various problems proposed, such as the calculation of roots of a quadratic equation or problems of application to calculus and differential equations. This workshop allows the teacher to show many variants of the proposed exercises, without losing the generality of the functions to be worked on.